Medios de comunicación alternativos en el escenario digital de las protestas por el decreto 883 en Ecuador 2019 - Luzón Rocha, Ruth Abigail (2020)
New technologies have changed the expectation of alternative media, opening space to inform not only in a limited space, but go beyond. One of the most outstanding aspects are the social networks that have allowed the world to be connected to another level, the way to communicate, during the protests by decree 883, these new information mechanisms took center stage because it was the only means that allowed to provide real news. and immediate of what was happening at that time, the images and videos circulated in networks announced the sad story that Ecuador lived in those moments. The tune for these media increased and its prominence gained strength.